2017
DOI: 10.1002/lary.26776
|View full text |Cite
|
Sign up to set email alerts
|

Utility of preoperative fine needle aspiration in parotid lesions

Abstract: 4. Laryngoscope, 128:398-402, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 24 publications
3
50
1
4
Order By: Relevance
“…Adequate sampling, the application of ancillary tests (such as immunohistochemical studies), awareness of prior history of malignancy, and familiarity with metaplastic and atypical changes in both benign and malignant conditions may improve the diagnosis. Reviewing the case in multidisciplinary tumor boards and in intraoperative consultation and microscopic examination of frozen section of the neoplasm would assist the otolaryngologist in determining the optimal management of patients with SUMP …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate sampling, the application of ancillary tests (such as immunohistochemical studies), awareness of prior history of malignancy, and familiarity with metaplastic and atypical changes in both benign and malignant conditions may improve the diagnosis. Reviewing the case in multidisciplinary tumor boards and in intraoperative consultation and microscopic examination of frozen section of the neoplasm would assist the otolaryngologist in determining the optimal management of patients with SUMP …”
Section: Discussionmentioning
confidence: 99%
“…Fine‐needle aspiration (FNA) is a well accepted tool for the diagnosis and subsequent management of salivary gland mass lesions because of its accuracy in discrimination between nonneoplastic versus neoplastic entities, minimal invasiveness, and cost‐effectiveness . Overall, studies show from 60% to 97% sensitivity, from 81% to 95% specificity, and from 91% to 92% diagnostic accuracy for FNA of salivary gland lesions .…”
Section: Introductionmentioning
confidence: 99%
“…Despite of some disadvantages of FNA, patients may gain considerable profit by this diagnostic approach when providing conclusive results. 6 Particularly, early knowledge on the actual state of disease provides the possibility for precise planning of the extent of tumour resection and neck dissection and for early and accurate patient information. 7 Nishikawa and co-authors showed that performance of FNA or FS enables determination of tumour cell grading, which subsequently is a key factor for the planning of the extent of tumour resection.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative diagnosis of a parotid malignancy by biopsy may allow for optimal surgical planning, including preparation for total parotidectomy and/or facial nerve sacrifice if involvement is identified intraoperatively, and avoidance of conservative extracapsular dissection or excisional biopsy, subsequently improving the chances for adequate margin‐free resection and adequate nodal sampling . A recent single center study of 477 patients with surgically treated parotid masses who underwent FNA found that FNA changed the surgical management in 19% of patients, resulting in an added neck dissection when tumors were identified as malignant and downgrading to excisional biopsy in case of a benign entity …”
Section: Discussionmentioning
confidence: 99%